2021
DOI: 10.1186/s40662-021-00249-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rebound tonometer iCare IC200 as compared with IcarePRO and Goldmann applanation tonometer in patients with glaucoma

Abstract: Background This study investigated the agreement between a new rebound tonometer, IC200, and IcarePRO and Goldmann applanation tonometry (GAT). Methods This was a prospective cross-sectional study. We measured the intraocular pressure (IOP) in 145 eyes of 145 glaucoma patients in the sitting position using GAT, IcarePRO, and IC200. IcarePRO and IC200 measurements were also obtained in the supine position. IC200 measurement was performed using two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…Moreover, these IOP changes have been associated with an increase in nocturnal IOP and could be related to the progression of glaucoma. 20 In contrast to our results, Nakakura et al 21 , conducted a recent prospective cross-sectional study They used GAT, IcarePRO, and IC200 on 145 eyes of 145 glaucoma patients in the sitting and supine positions, and found no significant variations in IOP values between the sitting (13.3 mmHg) and supine positions (14.5 mmHg) for Icare PRO rebound tonometer, with difference (1.2 mmHg). Uzlu et al 22 , conducted a study on 49 eyes of 49 healthy children.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, these IOP changes have been associated with an increase in nocturnal IOP and could be related to the progression of glaucoma. 20 In contrast to our results, Nakakura et al 21 , conducted a recent prospective cross-sectional study They used GAT, IcarePRO, and IC200 on 145 eyes of 145 glaucoma patients in the sitting and supine positions, and found no significant variations in IOP values between the sitting (13.3 mmHg) and supine positions (14.5 mmHg) for Icare PRO rebound tonometer, with difference (1.2 mmHg). Uzlu et al 22 , conducted a study on 49 eyes of 49 healthy children.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies showed that the mean IOP difference between Icare PRO and GAT was between -0.38mmHg to 0.43mmHg [17][18]. As for the newest model of Icare the IC200, the mean IOP was approximately 3 mmHg lower than that of GAT IOP in a recent study by Nakamura et al [19].…”
Section: Discussionmentioning
confidence: 92%
“…ICare IOP values were lower by 3.1–4.0 mmHg than GAT values throughout follow-up points in our study. Several previous reports showed that ICare IOP values were lower by 0.4–3.0 mmHg than GAT values [ 29 , 30 , 31 , 32 ]. Our result is largely consistent with those previous reports.…”
Section: Discussionmentioning
confidence: 96%